(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Dengue virus infection is a serious health problem infecting 2.5 billion people worldwide. Dengue virus belongs to family Flaviviridae, having four serotypes that spread by the bite of infected Aedesmosquitoes. It causes a wide spectrum of illness from mild asymptomatic illness to severe fatal dengue haemorrhagic fever/dengue shock syndrome (DHF/DSS). The relationship of this country with dengue has been long and intense. The first recorded epidemic of clinically dengue like illness occurred at Madras in 1780 and the dengue virus was isolated for the first time almost simultaneously in Japan and Calcutta in 1943–1944. After the first virologically proved epidemic of dengue fever along the East Coast of India in 1963–1964, it spread to allover the country. The first full-blown epidemic of the severe form of the illness, the dengue haemorrhagic fever/ dengue shock syndrome occurred in North India in 1996. Aedesaegyptiis the vector for transmission of the disease. Vaccines or antiviral drugs are not available for dengue viruses; the only effective way to prevent epidemic dengue fever/dengue haemorrhagic fever (DF/DHF) is to control the mosquito vector, Aedesaegypti and prevent its bite. This country has few virus laboratories and some of them have done excellent work in the area of molecular epidemiology, immunopathology and vaccine development. Selected work done in this country on the problems of dengue is presented here. Dengue fever is a re-emergent and challenging public health problem in the world. In this review we will give an overview of the infectious DENV and will discuss the viral and host factors that are important in controlling DENV infection.